Financial and economic analysis of stingless bee farming in Malaysia - Abdurofi, Ilmas (2018)
As a reason factor affecting the present problematic advancement of beekeeping industry in Malaysia, the issues of high interest in rearing stingless bees (Trigona) is alternatively emerged by the local beekeepers. The Ministry of Agriculture and Agro-based Industry stated that the stingless honey bees may be a national super food due to its benefits to human bodies as there is a high demand in honey. Hence, the government tries to find ways to increase production in meeting the local demand as well as making it possible for export. Nevertheless, the recent information about financial, economic and policy approaches of stingless bees farming, are still limited. Therefore, the study initially aims to investigate socio-economic and cost-benefit analysis; financial appraisal; and level of competitiveness, comparative advantage and government policy of stingless bees farming in Malaysia. The study used primary data as input-output accounting figure from the existing farms and employed 124 stingless beekeepers as number observation. The data analysis applied cost benefit analysis, capital budgeting techniques and Policy Analysis Matrix (PAM). The finding showed the stingless bees farming’ benefits outweigh its costs, while labor cost constituted as a predominant concern in the cost of production and a high capital expenditure was expended by hive investment. Then, the Peninsula beekeeping farm generated highly profitable business, whilst Sarawak region showed efficient cost in the input-output, cost-benefit ratio and break-even analysis. Based on long term project assessment, the project was financially viable and swiftly recovered up its initial investment. The project also may sustained any possible risks in changing of certain micro-economic variables. Furthermore, the result of PAM model concluded that the industry achieved considerable competitiveness level at domestic and international market; indeed the resource use domestically was inexpensive. However, the government still did not intervene and let the industry run independently. Even though, some policies have been affected to some parts in Peninsular Malaysia, the effect on the market liberalization was not highly visible to the whole stingless bees farming in Malaysia. Therefore, the assistance from the government through a policy intervention is urgently needed.